2023
DOI: 10.2217/fon-2022-1133
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes in non-small-cell lung cancer patients with MET Exon 14 skipping mutation and brain metastases treated with capmatinib

Abstract: Aim: To assess real-world clinical outcomes in patients with non-small-cell lung cancer with MET exon 14 skipping mutation and brain metastases (BM) who received capmatinib, a recently approved MET inhibitor, in routine US clinical practice. Materials & methods: Patient data were collected using a retrospective medical record review, led by participating oncologists. Eligible patients initiated treatment with capmatinib in any line, after BM diagnosis, between May 2020 and June 2021. Data on real-world ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…The VISION study reported a case (0.7%) of maculopapular rash in MET -mutant NSCLC ( 6 ), whereas no such cases were reported in the GEOMETRY mono-1 study ( 7 ). In a recent real-world study by Paik et al , less than 20% of the patients discontinued treatment, and among them, 90% were attributed solely to PD ( 8 ). These data indicate a considerably low probability of treatment discontinuation caused by the appearance of skin rash in MET -mutant NSCLC.…”
Section: Discussionmentioning
confidence: 97%
“…The VISION study reported a case (0.7%) of maculopapular rash in MET -mutant NSCLC ( 6 ), whereas no such cases were reported in the GEOMETRY mono-1 study ( 7 ). In a recent real-world study by Paik et al , less than 20% of the patients discontinued treatment, and among them, 90% were attributed solely to PD ( 8 ). These data indicate a considerably low probability of treatment discontinuation caused by the appearance of skin rash in MET -mutant NSCLC.…”
Section: Discussionmentioning
confidence: 97%
“…As for patients with the cMET exon 14 skipping mutation, retrospective real-world data show promising results with either crizotinib treatment (mPFS 12.4 months, mOS 22.8 months) or capmatinib therapy (mPFS 9.5 months, mOS 18.2 months) [ 47 , 48 ]. Moreover, a substantial benefit is noted when using the MET inhibitor capmatinib in patients with brain metastases, demonstrating an 85% response rate both systemically and intracranially, even without the primary use of radiotherapy [ 49 ]. These data are further confirmed by the meta-analysis, which proved a high intracranial response rate of 95% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the real-world overall response rate and real-world progression-free survival were even better. In patients treated with first-line capmatinib (like me), the overall response rate was 90.9% systemically and 87.3% intracranially (brain metastasis), with median systemic progression-free survival (PFS) was 14.1 months [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It takes expended time (PFS) for cells with pre-exiting R1 mutation to multiply to radiologically significant number, to make progression visible radiologically. (For example, monotherapy with capmatinib for my condition offers PFS of 14.1 months [ 20 ]). But invisible progression takes place during therapeutic response: MET+R1-cells are replacing MET-cells ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%